Valorisation of biolymers from biomass waste for the formulation and devlopment of high added value composite materials - BOUSSETTA ABDELGHANI (Faculté des Sciences et des Techniques, Béni Mellal - Doctorat ou Doctorat National, 2023)
______
Keywords: 1. Natural Sciences; 1.5 Earth and related environmental sciences